Innovations favouring environmental sustainability in avocado orchards: an analysis of the Spanish Mediterranean coastlands - Sayadi, S.; Calatrava Requena, J.; Guirado Sánchez, E. (Spanish Journal of Agricultural Research, 2005)
Avocado cultivation started to take hold on the Southern Spanish Mediterranean coast in the early 1970s. Today, avocado is the most widespread tropical crop in the area, occupying some 8,350 ha; average annual production is around 70,000 Mg. In recent years, several technological innovations have been adopted by avocado growers, some of which favour the environmental sustainability of the crop. Among the practices adopted are several non-tillage or conservation tillage techniques (which use no or very little herbicide), flower pruning, the use of weed clearing machines, mulching, and organic and integrated farming systems. This paper reports the results of a survey of avocado growers from the southeastern coast of Spain, and analyses their adoption of environmentally friendly technologies. To identify the grower and orchard characteristics that encourage such adoption, an aggregate innovation index was created and a multinomial ordered probit model constructed. The findings might help in the design of strategies for increasing the adoption of environmentally safe technologies.